2005
DOI: 10.1111/j.1365-2109.2004.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ammonia and nitrite on survival, growth and moulting in juvenile tiger crab, Orithyia sinica (Linnaeus)

Abstract: The e¡ects of ammonia and nitrite on survival, growth and moulting were investigated in juvenile tiger crab, Orithyia sinica (carapace length 3.91 AE 0.15 mm, carapace width 3.84 AE 0.23 mm, n 5 440), after 30 days exposure to ammonia-N (0, 20, 50, 100 and 150 mg L À 1 ) and nitrite-N (0, 50, 100, 150, 200 and 250 mg L À 1 ) using a continuous £ow system. Survival rates of tiger crab exposed to ammonia and nitrite decreased linearly with the exposure time and concentration. The growth rate of tiger crab expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…10) Although nitrite and ammonia tolerance differs among different aquatic animals, they are toxic to fish (Tabata 1962), shrimps (Lin et al 1993;Ostrenskya and Wasielesky 1995), juvenile and adult crabs (Zhao et al 1997;Seneriches-Abiera et al 2007;Romano and Zeng 2007;Koo et al 2005) and Artemia (Chen et al 1989 2007), but higher than those of Z 1 (2.736 mg/l) and Z 2 (11.541 mg/l) of P. trituberculatus (Lu et al 2006). Comparing the nitrite LC 50 values of larvae of different crabs (Table 3), it is found that the total 96-h LC 50 ammonia values of Z 1 (11.16 mg/l, Fig.…”
Section: Effects Of Ammonia-n On Survival Rate Of Zmentioning
confidence: 96%
See 1 more Smart Citation
“…10) Although nitrite and ammonia tolerance differs among different aquatic animals, they are toxic to fish (Tabata 1962), shrimps (Lin et al 1993;Ostrenskya and Wasielesky 1995), juvenile and adult crabs (Zhao et al 1997;Seneriches-Abiera et al 2007;Romano and Zeng 2007;Koo et al 2005) and Artemia (Chen et al 1989 2007), but higher than those of Z 1 (2.736 mg/l) and Z 2 (11.541 mg/l) of P. trituberculatus (Lu et al 2006). Comparing the nitrite LC 50 values of larvae of different crabs (Table 3), it is found that the total 96-h LC 50 ammonia values of Z 1 (11.16 mg/l, Fig.…”
Section: Effects Of Ammonia-n On Survival Rate Of Zmentioning
confidence: 96%
“…Several studies on toxicity of ammonia have been reported (Colt and Tchobanoglous 1978;Tabata 1962), such as effects of ammonia on Artemia nauplii (Chen et al 1989), effects of ammonia on zoeae, mysis, postlarvae and late juveniles stages of Penaeus japonicus (Lin et al 1993), effects of ammonia on embryos, nauplii, zoeae, myses and postlarvae stages of the Penaeus paulensis (Ostrenskya and Wasielesky 1995), effects of ammonia on zoea 1, zoea 2, and juvenile of Eriocheir sinensis (Zhao et al 1998), effects of ammonia on zoea 1, zoea 5 and megalop of S. serrata (Neil et al 2005), and effects of ammonia on juvenile Orithyia sinica (Koo et al 2005), and effects of ammonia on early juvenile P. pelagicus (Romano and Zeng 2007). Several studies on toxicity of nitrite have been reported (Seneriches-Abiera et al 2007), such as effects of nitrite on Artemia nauplii (Chen et al 1989), acute toxicity of nitrite on early larval stages of S. serrata (Seneriches-Abiera et al 2007), acute toxicity of nitrite on zoeae and megalop stages of P. trituberculatus (Lu et al 2006), and effects of nitrite on juvenile Orithyia sinica (Koo et al 2005), and effects of nitrite on early juvenile P. pelagicus (Romano and Zeng 2009). Several studies on moulting of larvae (Liao et al 2001;Josileen and Menon 2004) and early juvenile (Romano and Zeng 2006;2009) of P. pelagicus have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia (NH 3 refers to molecular ammonia, NH 4 + to ammonium irons, and ammonia to the sum of both) is highly toxic in most aquatic animals, which can affect a variety of physiological functions of crustaceans including the respiration, metabolism, nervous system, immune system, osmoregulation, excretion, molting and growth, and even lead to death (Marcaida et al, 1992;Chen and Nan, 1993;Chen et al, 1994;Chen and Lin, 1995;Chen and Chen, 1996;Rebelo et al, 1999;Racotta and Hernandez-Herrera, 2000;Cheng and Chen, 2002;Koo et al, 2005). In comparison to the research on how aquatic animals deal with the excess of ambient or internal ammonia during exposure to ammonia-N, such as glutamine formation (Wicks and Randall, 2002;Hong et al, 2007), detoxification of ammonia to urea or uric acid (Greenaway and Raghaven, 1998;Lee and Chen, 2004;Bernasconi and Uglow, 2011), and reduction in the rate of proteolysis and the rate of amino acid catabolism (Lim et al, 2001), very little is known about branchial ion and ammonia transports in crustaceans.…”
Section: Introductionmentioning
confidence: 98%
“…On the third day, the ammonia concentration in the sea water reached 0.8 ppm, an extremely toxic level for most marine fishes and crustaceans. The concentration of ammonia in the water is one of the main environmental problems faced by marine organisms (Koo et al, 2005;Neil et al, 2005), affecting their osmoregulation metabolism by raising the competition with potassium ion in membrane of osmoregulatory gills (Weihrauch et al, 2004). Although it was not possible to conduct pathological analyses to the determination of lesions in gills in the captured specimens, the burying latency did not seem to be affected in the mole crabs captured in the third day.…”
Section: Discussionmentioning
confidence: 99%